A highly sensitive, foldable and wearable pressure sensor based on MXene-coated airlaid paper for electronic skin. Issue 37 (20th August 2021) - Yao, Di-Jie; Tang, Zhenhua; Zhang, Li; Liu, Zhi-Gang; Sun, Qi-Jun; Hu, Song-Cheng; Liu, Qiu-Xiang; Tang, Xin-Gui; Ouyang, Jianyong
Abstract : MXene-coated airlaid paper sensors were fabricated via the dip-coating technique, displaying high sensitivity (7.65 kPa −1 ), broad sensing range (300 kPa) and durability for human motion monitoring and 3D folded conformational change detection. Abstract : Electronic textiles (E-textiles) have received extensive attention for use in human motion detection, wearable electronics, and artificial intelligence. However, fabrication costs and methodology are still key issues preventing the commercialization of highly sensitive and wearable sensors. Here, simple to prepare low-cost conductive MXene-coated airlaid paper (MXene AP) sensors were fabricated via a dip-coating technique for use as electronic skin. The two-layer MXene AP sensors with a three-dimensional structure display high sensitivity (7.65 kPa −1 at 0–3.3 kPa), a broad sensing range (up to 300 kPa), and a stable response for more than 1000 cycles, presenting good sensitivity, repeatability, and durability, and their mechanism was investigated. Furthermore, origami technology can be used to fold MXene AP into an arbitrary shape with good sensing performance, and multistate conformational changes and simulated human touch can also be detected using the resultant three-dimensional (3D) MXene AP sensors. The wearable MXene AP sensors can be used to monitor human body motion and to collect human physical signals sensitively and accurately in the form of electronic skin. These strategies of folding and layering textile-decorated conductive nanomaterials provide a reference for next-generation textile-based wearable electronics and electronic skin.